LAS BASES DE DATOS COMO HERRAMIENTA PARA LA INVESTIGACIÓN HISTÓRICA - Malavassi Aguilar, Ana Paulina (2012)
The purpose of these introductory notes is to present briefly the advantages and possible limitations associated with using databases for historical research, to finish explaining, at length, a product built based on the lifting of various primary sources.